STRATEGI PEMASARAN KONTEN INSTAGRAM : ANALISIS WINEED.ID DALAM MENINGKATKAN INTERAKSI DAN KEPUTUSAN PEMBELIAN - Syifaur Rohmah, Nabila; Taufik, Muchamad; Mubarok, Diki (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study analyzes the content marketing strategy used by @Wineed.id to enhance consumer engagement and purchasing decisions through the social media platform Instagram. In its enterprise, @Wineed.id applies three key concepts—modern feel, public relations, and direct marketing—as approaches to building relationships with consumers. The research method used in this study is descriptive qualitative, with primary data obtained directly from key informants through interviews. Through interviews and document analysis, the findings indicate that the level of content views has a significant impact on sales performance.